High-Yield Human Induced Pluripotent Stem Cell-Derived Monocytes and Macrophages Are Functionally Comparable With Primary Cells - Cui, Di; Franz, Alexandra; Fillon, Sophie A.; Jannetti, Linda; Isambert, Timo; Fundel-Clemens, Katrin; Huber, Heinrich J.; Viollet, Coralie; Ghanem, Alexander; Niwa, Akira; Weigle, Bernd; Pflanz, Stefan (Frontiers in Cell and Developmental Biology, 2021)
Macrophages are pivotal effectors of host immunity and regulators of tissue homeostasis. Understanding of human macrophage biology has been hampered by the lack of reliable and scalable models for cellular and genetic studies. Human iPSC-derived monocytes and macrophages, as an unlimited source of subject genotype-specific cells, will undoubtedly play an important role in advancing our understanding of macrophage biology and implication in human diseases. In this study, we present a fully optimized differentiation protocol of hiPSC-derived monocytes and GM-CSF or M-CSF macrophages. We present characterization of iPSC-derived myeloid lineage cells at phenotypic, functional and transcriptomic levels, in comparison with corresponding subsets of peripheral blood-derived cells. We also highlight the application of hiPSC-derived monocytes and macrophages as a gene-editing platform for functional validation in research, drug screening and potentially cell therapies.